Tipologi hadis: Klasifikasi hadis berdasarkan kualitas - Ilmiyah, Nahdliyatul; Sari, Dyna Evalina Prima; Agustin, Natasya Alicya (Maliki Interdisciplinary Journal, 2025)
English Hadith as the second source of religious knowledge after the Qur'an is considered important in determining the law in daily life. However, many people still do not understand the status and position of the hadith, whether it is sahih, hasan, or dhaif, and whether it can be used as proof. This article examines the quality of traditions based on the quality of the narrators and the quality of the text. Qualified traditions are considered maqbul, divided into sahih and hasan, while those that do not qualify are mardud. Similarly, traditions are viewed in terms of their quantity, with mutawatir traditions being considered stronger than Ahad traditions. The research method used is qualitative research with the type of literature study or library research. This literature study was conducted by accessing various references such as scientific journals, books, and articles related to the typology of hadith based on quality. The results of this article understand that the classification of hadith based on the quality of the narrators strung in the sanad and the quality of the matan is important to understand in determining the validity of a hadith.